Pengaruh Kepercayaan Diri dan E-Recruitment terhadap Minat Melamar Kerja: (Studi pada Fresh Graduate Gen Z di Kabupaten Tasikmalaya) - Nina Nurjanah; Ardhiansyah Ardhiansyah (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
In the digital era, job-seeking mechanisms have evolved through e-recruitment platforms, particularly for Gen Z fresh graduates. However, seamless digital access does not inherently trigger a high intention to apply for jobs, suggesting a complex interplay between internal psychological states and external technical factors. Objective: This investigation empirically examines the extent to which self-efficacy and the effectiveness of e-recruitment systems influence the intention to apply for jobs among Gen Z fresh graduates in Tasikmalaya Regency. Methodology: This study employed an explanatory quantitative approach involving 80 subjects selected via purposive sampling. Data evaluation was conducted through Multiple Linear Regression analysis using SPSS software. Findings: The research data demonstrates that both self-efficacy and digital recruitment systems exert a positive and significant impact on job application intentions, both independently and simultaneously. Furthermore, self-efficacy was identified as a more dominant predictor compared to recruitment technology. An R-Square value of 0.590 indicates that these two variables account for 59% of the variation in job application intentions. Implications: Companies are encouraged to continuously modernize their recruitment infrastructure while considering the psychological readiness of applicants and strengthening corporate branding to attract high-potential new graduates.